Signifikansi Kompetensi Guru Pak Dalam Meningkatkan Mutu Pembelajaran Peserta Didik - Titi Kurniawati Harefa; Sozanolo Z (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
the teacher is an educator whose role is to educate, train and evaluate students so that they have the knowledge, ability, noble caracter and think smart. With the existense of educators, theyare able to create aa qualifiednext generation to lead the nation. An conten educator has competence in teaching and increasing the learning interest of his students. A teacher is also one of determinants of success in the world of education stands on love, service, and formation man is in convormity with and in the image of God. The establishment of a christian school is the implementation of the great commission of christ. The specific goal is for everyone to experience an encounter with christ and experience renewal for everyone’s life continously. The method used bythe author in this study is a qualitative method, (library research). Where the author collect library books as the main source, journals,articles, and also websites related to the title. The goal to be achieved in this writing is to open our horizons, especially teachers or those who want to become teachers, so that they have professional values in carrying out and carrying out their vocation when educating and teaching students. The results obtained from this study are that teacher professionalism can help students realize their goals, and there is the potential for teachers to be the spearheads who bring big changes to nation and state.